On the Doorstep of Europe : Asylum and Citizenship in Greece - Cabot, Heath (Book collections on Project MUSE., 2014)
On the Doorstep of Europe examines the way asylum seekers, bureaucrats, and service providers in Greece attempt to navigate the dilemmas of governance, ethics, knowledge, and sociability that emerge through this legal process.